Serum creatine kinase after intramuscular injections. Issue 717 (July 1985) - Konikoff, F.; Halevy, J.; Theodor, E.
Abstract : Serum creatine kinase (CK) activity was measured after intramuscular injections in 44 patients hospitalized for non-cardiac reasons. The drugs injected were: diazepam, dipyrone, metoclopramide, meperidine, pentazocine and procaine penicillin. Only 3 out of 44 patients (7%) demonstrated significant elevation of CK levels following the intramuscular injections. In these 3 patients the elevation was mainly due to a rise of the MM-isoenzyme fraction with MB levels increased in one patient. These findings do not justify the common clinical notion of regarding intramuscular injections as a frequent cause of serum CK elevation. It is concluded that high CK serum values in a patient with chest pain should always be considered with utmost suspicion, disregarding the possible effects of a previous intramuscular injection.